Developing Reading Supplementary Materials Using Islamic Stories for An Extracurricular Program of Islamic Senior High School Level - Ani Sukma Sari (Language-Edu, 2019)
AbstractThe fundamental aim of this study was to develop reading supplementary materials using Islamic stories for an extracurricular program of senior high school level. This present study used Research and Development (R&D) design adopted from Borg & Gall (2003). Hence, several scientific procedures involved in this development were: needs analysis, studying recent theories, developing the educational product, validating the product to the experts, revision, try out and final product. Then, the final product of this present study is an exercise book of reading materials focusing on enhancing students’ interest in reading since this educational product is developed based on the students’ need and interest as Islamic learners. Perfectly, this developed product is also completed with several reading strategies and techniques to help the students in reading such as scanning and skimming, More, vocabulary exercises are also provided for the students in each unit of the book in order to   Last but not the least, the final result of this study revealed that the students enthusiastically showed their interest and actively engaged in reading activities through this material development. Keywords: developing, reading supplementary materials, Islamic stories, extracurricular